2017
DOI: 10.2147/ijn.s130565
|View full text |Cite
|
Sign up to set email alerts
|

Physiological origin of biogenic magnetic nanoparticles in health and disease: from bacteria to humans

Abstract: The discovery of biogenic magnetic nanoparticles (BMNPs) in the human brain gives a strong impulse to study and understand their origin. Although knowledge of the subject is increasing continuously, much remains to be done for further development to help our society fight a number of pathologies related to BMNPs. This review provides an insight into the puzzle of the physiological origin of BMNPs in organisms of all three domains of life: prokaryotes, archaea, and eukaryotes, including humans. Predictions base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 199 publications
(297 reference statements)
0
50
0
15
Order By: Relevance
“…Biogenic magnetic nanoparticles have been reported in various human organs, including the heart, liver, spleen, adrenal glands, ethmoid bone, and brain. [ 64 ] Magnetic remanence (residual magnetism) has been identified recently in the human body, particularly in the brain. [ 65 ] Magnetite is preferentially partitioned in the human brain, specifically in the cerebellum and brain stem.…”
Section: Microbe‐mediated Mineralization In Naturementioning
confidence: 99%
“…Biogenic magnetic nanoparticles have been reported in various human organs, including the heart, liver, spleen, adrenal glands, ethmoid bone, and brain. [ 64 ] Magnetic remanence (residual magnetism) has been identified recently in the human body, particularly in the brain. [ 65 ] Magnetite is preferentially partitioned in the human brain, specifically in the cerebellum and brain stem.…”
Section: Microbe‐mediated Mineralization In Naturementioning
confidence: 99%
“…In 2016 Maher et al [72] showed two types of magnetite in the brains of persons with dementia: euhedral biogenic particles and spherical exogenous particles most likely arising from air pollution. Magnetite in tissue paradoxically serves essential life functions while in excess or from external sources causes harmful effects and disease [130].…”
Section: Magnetite -Iron Oxide Nanoparticles -And the Heartmentioning
confidence: 99%
“…An excess of labile iron related to the inability of ferritin to retain iron in its core may represent an additional iron supply for magnetic nanoparticle biomineralization [130]. Iron oxide nanoparticles, but not zerovalent iron nanoparticles or coated iron oxide particles can cross plasma membranes.…”
Section: Magnetite -Iron Oxide Nanoparticles -And the Heartmentioning
confidence: 99%
“…Зважаючи на те що механізм біомінералізації біогенних магнітних наночастинок (БМН) єдиний для представників усіх царств живих організмів (бактерій, архей та еукаріотів [29][30][31]), важливо дослідити, чи є мікроорганізми активного мулу потенційними продуцентами БМН.…”
Section: вступunclassified